Qatar Foundation Annual Research Forum Volume 2012 Issue 1 2012
DOI: 10.5339/qfarf.2012.bmos2
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of of polycystic ovary syndrome among reproductive females in the state of Qatar: A cross-sectional study

Abstract: Background & Objectives: Stein-Leventhal syndrome commonly known as polycystic ovary syndrome (PCOS) is the most common endocrinopathy among reproductive females. PCOS is a multisystem challenge causing not only gynecological issues such as irregular menstrual cycles, hyperandrogenism and infertility but also causing insulin resistance, type 2 diabetes and cardiovascular diseases. The objective of our study was to determine the incidence of PCOS among reproductive females at Qatar University using the Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Of particular note, a few papers measured the local prevalence in Qatar, [16] Oman, [17] Egypt, [18,19] Iran, [20] and Syria [21]. For the Gulf region, a total of 7 articles in the Gulf Council Countries (GCC) are found addressing PCOS prevalence in the literature as of 2022, [16,17,[22][23][24][25][26] one of which was conducted in Ras Al Khaimah (RAK), UAE. [26] There are only a few available studies evaluating PCOS awareness in the MENA region, either as a primary or a secondary objective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular note, a few papers measured the local prevalence in Qatar, [16] Oman, [17] Egypt, [18,19] Iran, [20] and Syria [21]. For the Gulf region, a total of 7 articles in the Gulf Council Countries (GCC) are found addressing PCOS prevalence in the literature as of 2022, [16,17,[22][23][24][25][26] one of which was conducted in Ras Al Khaimah (RAK), UAE. [26] There are only a few available studies evaluating PCOS awareness in the MENA region, either as a primary or a secondary objective.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies found, one study investigated the region-wide prevalence of PCOS in the MENA region, reporting a point prevalence of 2079.7 per 100,000 in 2019 [15]. Of particular note, a few papers measured the local prevalence in Qatar, [16] Oman, [17] Egypt, [18,19] Iran, [20] and Syria [21]. For the Gulf region, a total of 7 articles in the Gulf Council Countries (GCC) are found addressing PCOS prevalence in the literature as of 2022, [16,17,[22][23][24][25][26] one of which was conducted in Ras Al Khaimah (RAK), UAE.…”
Section: Introductionmentioning
confidence: 99%
“…[22] and Syria [23]. As of 2022, a total of 7 articles in the Gulf Council Countries (GCC) were found addressing PCOS prevalence, [18,19,[24][25][26][27][28] one of which was conducted in Ras Al Khaimah (RAK), UAE. [28] Available studies on PCOS in the MENA region have not addressed awareness among the general population until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Among the studies found, one study investigated the region-wide prevalence of PCOS in the MENA region, reporting a point prevalence of 2079.7 per 100,000 in 2019 [17]. Some other notable studies measured local prevalence in Qatar, [18] Oman, [19] Egypt [20,21] , Iran. [22] and Syria [23].…”
Section: Introductionmentioning
confidence: 99%